2018
DOI: 10.1016/j.stem.2018.04.021
|View full text |Cite
|
Sign up to set email alerts
|

An Intermediate Pluripotent State Controlled by MicroRNAs Is Required for the Naive-to-Primed Stem Cell Transition

Abstract: The embryonic stem cell (ESC) transition from naive to primed pluripotency is marked by major changes in cellular properties and developmental potential. ISY1 regulates microRNA (miRNA) biogenesis, yet its role and relevance to ESC biology remain unknown. Here, we find that highly dynamic ISY1 expression during the naive-to-primed ESC transition defines a specific phase of "poised" pluripotency characterized by distinct miRNA and mRNA transcriptomes and widespread poised cell contribution to mouse chimeras. Lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(38 citation statements)
references
References 50 publications
1
37
0
Order By: Relevance
“…To further compare the 5C‐Oct4GFP + cells with epiblast‐like cells (EpiLCs) and cells in formative state, previous reported datasets were downloaded and analyzed together with the current RNA‐Seq (Data ref: Hayashi et al , 2011; Data ref: Buecker, ; Data ref: Bertone, ; Data ref: Kalkan et al , ). Based on these datasets and previous reports (Hayashi et al , 2011; Kalkan et al , ; Smith, ; Du et al , ; Takahashi et al , ), cells in 5C state are quite different from EpiLCs and cells in formative state. Generally, cells in 5C state seldomly contributed to chimera and had high expression of glycolysis and mesenchymal markers (Fig EV3A).…”
Section: Resultssupporting
confidence: 56%
“…To further compare the 5C‐Oct4GFP + cells with epiblast‐like cells (EpiLCs) and cells in formative state, previous reported datasets were downloaded and analyzed together with the current RNA‐Seq (Data ref: Hayashi et al , 2011; Data ref: Buecker, ; Data ref: Bertone, ; Data ref: Kalkan et al , ). Based on these datasets and previous reports (Hayashi et al , 2011; Kalkan et al , ; Smith, ; Du et al , ; Takahashi et al , ), cells in 5C state are quite different from EpiLCs and cells in formative state. Generally, cells in 5C state seldomly contributed to chimera and had high expression of glycolysis and mesenchymal markers (Fig EV3A).…”
Section: Resultssupporting
confidence: 56%
“…Those different phenotypes between dgcr8 −/− and dKO ESCs during the naïve-to-primed transition suggest other miRNAs also participate in this transition. Recently, a study by Du and colleagues demonstrated a protein involved in the biogenesis of polycistronic miRNAs (such as miR-17~92 ), Isy1, is necessary for the naïve-to-primed transition [196]. A set of miRNAs, including miR-17~92 and miR-290 , were up-regulated during the naïve-to-primed transition under the positive regulation of Isy1 [196].…”
Section: Functions Of Mirnas In Stem Cellsmentioning
confidence: 99%
“…As an example, ISY1 gene expression during the naive-to-primed ESC transition determines a specific phase of ‘poised’ pluripotency. ISY1 promotes exit from the naive state and is necessary and sufficient to induce and maintain balanced pluripotency; however, persistent ISY1 overexpression inhibits the exit from the naive to the primed state [ 114 ].…”
Section: Permanent Reontogenesis or Rejuvenation Circlementioning
confidence: 99%